Impact of health insurance equity on poverty vulnerability: evidence from urban–rural health insurance integration in rural China - Li, Zhipeng; Chen, Yuqian; Ding, Jing (Frontiers in Public Health, 2023)
Background In 2016, the Chinese government introduced an integration reform of the health insurance system with the aim to enhance equity in healthcare coverage and reduce disparities between urban and rural sectors. The gradual introduction of the policy integrating urban and rural medical insurance in pilot cities provides an opportunity to evaluate the policy impact. This study attempts to assess the policy impact of urban–rural health insurance integration on the chronic poverty of rural residents and to analyze the mechanisms. Method Based on the four waves of data from the China Health and Retirement Longitudinal Study (CHARLS) conducted in 2011, 2013, 2015, and 2018, we employed a staggered difference-in-differences (staggered DID) model to assess the impact of integrating urban–rural health insurance on poverty vulnerability among rural inhabitants and a mediation model to analyze the mechanism channel of the policy impact. Results (1) Baseline regression analysis revealed that the urban–rural health insurance integration significantly reduced the poverty vulnerability of rural residents by 6.32% (p < 0.01). The one health insurance system with one unified scheme of contributions and benefits package (OSOS, 6.27%, p < 0.01) is more effective than the transitional one health insurance system with multiple schemes (OSMS, 3.25%, p < 0.01). (2) The heterogeneity analysis results showed that the urban–rural health insurance integration had a more significant impact on vulnerable groups with relatively poor health (7.84%, p < 0.1) than those with fairly good health (6.07%, p < 0.01), and it also significantly reduced the poverty vulnerability of the group with chronic diseases by 9.59% (p < 0.01). The integration policy can significantly reduce the poverty vulnerability of the low consumption and low medical expenditure groups by 8.6% (p < 0.01) and 7.64% (p < 0.01), respectively, compared to their counterparts. (3) The mechanism analysis results showed that the urban–rural health insurance integration can partially enhance labor supply (14.23%, p < 0.01) and physical examinations (6.28%, p < 0.01). The indirect effects of labor supply and physical examination in reducing poverty vulnerability are 0.14%, 0.13% respectively. Conclusion The urban–rural health insurance integration policy significantly reduced poverty vulnerability, and the OSOS is more effective than the OSMS. The urban–rural health insurance integration policy can significantly reduce poverty vulnerability for low consumption and poor health groups. Labor supply and physical examination are indirect channels of the impact. Both channels potentially increase rural household income and expectations of investment in human health capital to achieve the policy objective of eliminating chronic poverty.